O professor universitário, sem formação pedagógica, e a origem e construção de sua práxis docente: que racionalidade? Que caminhos? - Andrade, Telga Persivo Pontes de (2006)
We approach about the docent knowledge that is the center of the international researches. Through the narrative of the life stories, of semi-structured interviews, among other instruments of mediation, we tried to understand the sense of the speeches of 20 teachers or public and private universities of Fortaleza- Ceará -Brazil, dismissed of pedagogic formation, regarding the origin of their knowledge, ways of being and doing; their conception about how, when and with who they leaned how to teach. We still intend to construct to a theoretical picture on docent knowledge and an illustration of the multiple facets and origin of this. It was our intention also to establish a parallel between the imaginary of the citizens and the socialepistemological theory of Maurice Tardif. We tried to comprehend the sense of the speeches of our collaborators in an active and creative way, following the dialogical and polyphonically perspective of Bakhtin. We understand that the imaginary of these teachers is constituted by a myriad of beliefs, conceptions, values and feelings, instead mutable, dialectical and dynamic. In their set of ideas about knowledge of these teachers have diverse sources and a lot characteristics, witch was identified by the research in individual speeches of the professors of the university. We identified three characteristics of this knowledge: witch the firs is self-learning pratice, witch was based on a gift; or consider as art the knowledge pratice; or in a disciplinal identity witch was consider the knowledge of the subject as primordial. In the imaginary, the collaborators, they judge to have learnt to teach practicing; they also believe that their knowledge are built and rebuilt, , to cross by the voices of relatives, teachers and colleagues with whom they share their life experience through a dialogical relation. They consider also that the knowledge of the subject, as well as their ability of the professional practicing are essential for the exercise of the teaching activity, instead they agree that a knowledge isolated is not enough to forge a good teacher, because this one is made by the conjugation of diverse knowledge, acquired in and by the daily professional work of the teaching job, therefore, through their knowledge of experience, always mediated by the dialog with the diverse people with who they interact in their life and through a spontaneous communicative way, without which the education, the collective job, the cooperation are not possible. Knowing that or not, the teachers of graduation schools perpetuate medieval practices, by experimentation, without the certainty of their efficiency. The way for us, college teachers destitute of pedagogic formation, is to hold the hermeneutic dimension of pedagogy; it’s to develop a pedagogic rationality, a communicative and emancipator competence through a critic reflection of our daily professional work. Knowing that or not this professors had a pratice, an speech and a original pedagogy theory, witch was builded on real teach situation and we believe that should be consider on the educational research.